Positive impacts of perceived social support on prosocial behavior: the chain mediating role of moral identity and moral sensitivity - Li, Qiangqiang; Hu, Gengdan (Frontiers in Psychology, 2023)
The relationship between mental health and perceived social support has been well-established in previous studies. While previous research indicates that perceived social support is related to prosocial behavior, the mechanisms underlying this relationship remain unclear. In order to address this gap, a recent study investigated the mediating effects of moral identity and moral sensitivity on the relationship between perceived social support and prosocial behavior. Specifically, the study surveyed 978 college students using a questionnaire to examine the relationship between these variables. The results of the study showed that, after controlling for gender and age, perceived social support, moral identity, and moral sensitivity were significantly and positively correlated, all of which were also significantly and positively related to prosocial behavior. In addition, the study found that perceived social support was able to influence prosocial behavior through both independent mediation by moral identity and moral sensitivity, as well as through chain mediation.The findings of this study contribute to our understanding of the factors that shape prosocial behavior and offer suggestions for promoting such behavior in individuals.